A study of possibility of cross transmission for some Cryptosporidium spp. which isolated from birds to human through Experimental infection in laboratory mice - Ikhlas A. Al-Zubaidy; Ghaidaa A. Jasim (Al-Qadisiyah Journal of Pure Science, 2018)
The present study aimed to investigate of host specificity and know how incidence of cross transmission of Cryptosporidiosis which infected birds to human through tested incidence of experimental infection with Cryptosporidium spp. which isolated from birds in white mice balb/c . To attainment this purpose a laboratory mice were dosage with difference species of cryptosporidium which isolated from wild and domestic birds and then we determinate of susceptible of age group to infection and histological changes in experimentally infected mice. Laboratory mice divided into two age's group: Immature and mature mice , experimentally groups were gave a limited infection dose orally for each species of parasite (1X103oocyst / mouse).Result showed that cross transmission could happened for three species of Cryptosporidium that infected birds to lab. mice which are: C.parvum,C.meleagridis and C.baileyi with total ratio 30% and showed a significant difference compared with control group , and the results record a mortality ratio in infected mice (7.5%). The probability of mammalian infection by Cryptosporidium species which isolated from birds in our study represent the first record in Iraq. C.parvum and C.meleagridis showed loss of host specificity whereas C.baileyi was opportunist in his ability to infect another host beside their ordinary host (birds), while C.galli showed a high specificity for its host. The results showed a distinction of immature mice on mature mice with a significantdifference (35% vs 25%).The histological sections of intestine from infected mice showed : one of parasite's phase was adhere to epithelial cells and noted a histological changes which included: cohesion of neighboring villi , dwarf of villus , necrosis of their top and infiltration of inflammation cells nearby infection regions.